Peran Sistem Informasi Dukcapil Oloh Itah (SI-DOI) dalam Meningkatkan Transparansi dan Efisiensi Layanan di Dinas Kependudukan dan Catatan Sipil Kota Palangka Raya - Annisah Annisah; Tri Yani Otavia; Ropikah Ropikah; Tamara Salsabila; Kamal Hasuna (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
The Oloh Itah Dukcapil Information System (SI-DOI) is an innovation that aims to increase the efficiency and transparency of services at the Population and Civil Registration Service (Disdukcapil) of Palangka Raya City. This research aims to analyze the extent to which SI-DOI has achieved this goal. The research method used is a qualitative descriptive method, where research using a qualitative approach method is used to examine objects, individuals or organizations, conditions and systematics of a phenomenon that occurs, then analyze and describe the phenomenon that occurs regarding the role of the Oloh Itah Dukcapil Information System. (SI-DOI) In Increasing Transparency and Efficiency of Services at the Population and Civil Registry Service of Palangka Raya City. The research results show that SI-DOI has succeeded in contributing positively to the transparency and efficiency of services at the Palangka Raya City Population and Civil Registry Service. Even though there are challenges, the implementation of this information system can be considered quite successful and provides benefits to society and the government.